Transcatheter embolization for idiopathic peripheral pulmonary arterial aneurysm: A case report - Tamura, Tomoki (Clin Case Rep, 2019)
The natural history of idiopathic peripheral pulmonary arterial aneurysms (PAAs) is unclear; however, they can cause sudden death by rupture. Our case illustrates the utility and low invasiveness of transcatheter embolization using an AMPLATZER™ Vascular Plug 4 and hydrogel‐coated metallic coils in patients with idiopathic peripheral PAAs.